2014
DOI: 10.1186/1556-276x-9-234
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of chemical transformations of thiophenylglycoside of muramyl dipeptide on the fumed silica surface using TPD-MS, FTIR spectroscopy and ES IT MS

Abstract: In this study, chemical transformations of benzyl ester of О-(phenyl-2-acetamido-2,3-dideoxy-1-thio-β-d-glucopyranoside-3-yl)-d-lactoyl-l-alanyl-d-isoglutamine (SPhMDPOBn) on the fumed silica surface were examined, and the surface complex structure was characterized by temperature-programmed desorption mass spectrometry (TPD-MS), infrared spectroscopy (FTIR) and electrospray ion trap mass spectrometry (ES IT MS). Stages of pyrolysis of SPhMDPOBn in pristine state and on the silica surface have been determined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“…There was a broad weak absorption peak at 3 400–3 000 cm −1 with a lower response value, which was ν hydrogen-bonded silanols (overlapping the stretching modes in hydrogen-bonded hydroxyl bands produced by OH bonds adsorbed water and Si-OH). It showed that there was a small amount of isolated –OH on the surface of nSiO 2 , which helped to form hydrogen bonds between the hydroxyl groups of nSiO 2 and the hydroxyl groups of polysaccharides ( Azizova, Kulik, Palianytsia, Zemlyakov, Tsikalova & Chirva, 2014 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…There was a broad weak absorption peak at 3 400–3 000 cm −1 with a lower response value, which was ν hydrogen-bonded silanols (overlapping the stretching modes in hydrogen-bonded hydroxyl bands produced by OH bonds adsorbed water and Si-OH). It showed that there was a small amount of isolated –OH on the surface of nSiO 2 , which helped to form hydrogen bonds between the hydroxyl groups of nSiO 2 and the hydroxyl groups of polysaccharides ( Azizova, Kulik, Palianytsia, Zemlyakov, Tsikalova & Chirva, 2014 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The broad peak in the FTIR spectra at 3400 cm –1 for all three samples (NO, SNO, and FNO) is attributed to the symmetric stretching of the hydroxyl group . The transmittance intensity of this peak was the least for FNO, which suggests the modification of the surface OH groups during functionalization.…”
Section: Resultsmentioning
confidence: 89%
“…The broad peak in the FTIR spectra at 3400 cm −1 for all three samples (NO, SNO, and FNO) is attributed to the symmetric stretching of the hydroxyl group. 49 The trans-mittance intensity of this peak was the least for FNO, which suggests the modification of the surface OH groups during functionalization. The presence of stretching vibrations for CO, SiO, and SiC at 1720, 900, and 1130 cm −1 , respectively, in SNO and FNO differentiates these materials from NO.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The FTIR spectrum of CuO/HMS shows a broad absorption around 3600–3200 cm −1 ascribed to the overlapping of the O−H stretching of adsorbed water bands and silanols (Figure S3 in the Supporting Information) . The band observed near 1640 cm −1 corresponds to the bending mode of vibration of −OH groups of adsorbed water .…”
Section: Resultsmentioning
confidence: 98%